Comparative Study of the Use of PowerPoint and Prezi Media on Science Learning Outcomes - Purwantiningsih, Budi; Ilmiya , Nur Wachidatul; Arifin, Nayla Najma; Arifin, Moh. Bahak Udin By (Universitas Muhammadiyah Sidoarjo, 2025)
The IPAS (Natural Sciences and Social Studies) learning process for fifth grade students at MI Ma'arif Sambiroto still uses lecture methods and conventional learning media such as whiteboards, which results in a lack of interaction and active participation from students. This makes the learning atmosphere feel monotonous and students tend to get bored quickly, resulting in a less than optimal understanding of the material. This study aims to compare the use of PowerPoint and Prezi presentation media on the learning outcomes of fifth-grade students in IPAS. This study uses a quantitative research design with a quasi-experimental type and a nonequivalent control group design model. Data collection techniques were carried out through questionnaires, which were then analyzed using percentage analysis and One-Way Anova. The results showed that the use of PowerPoint media obtained 98% data, which was classified as good, while Prezi obtained 92% data, which was also classified as good. The learning outcomes of students who used PowerPoint were very high, with 91.7% data, and students who used Prezi obtained 91.4% learning outcomes.The One-Way ANOVA statistical test shows a significant difference between the two media in terms of IPAS learning outcomes, with a calculated F value of 125.364 for PowerPoint and 180.134 for Prezi. Based on these results, it can be concluded that although both media improve student learning outcomes, the use of PowerPoint has a higher value than Prezi in improving IPAS learning outcomes. Both media have a significant effect on IPAS learning outcomes.